Islamic criminal law: A Comparison Of its Application in Indonesia and Other Countries - Maswandi, Maswandi; Jamillah, Jamillah; Duha, Junindra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The crucial issue in grounding Islamic criminal law is that there are still many Islamic criminal law terms that use Arabic terms and Arabic backgrounds, so that Islamic criminal law is only considered to fit the Arabic context. And in Islamic law criminal law is called jinayah which is defined as actions prohibited by shara' which are threatened by Allah SWT with jarimah (punishment) hudud, qishas and diat or ta'zir, in other words, doing or not doing is only considered a criminal offense if a penalty has been determined and threatened against it. The type of research used is qualitative research with comparative descriptive method. The data collection technique in this research is the literature method, which traces the existing literature and carefully examines the data related to the issues discussed. The results of this study are the criminal laws of Indonesia, Malaysia and Brunei Darussalam as regulated in Qanun No. 14 of 2003 on Khalwat (Mesum), Enakmen Jenayah Syari'ah Selangor Number 9 of 1995 and Kanun Jenayah Syari'ah Brunei Darussalam 2013 have similarities and differences in terms of determining a criminal act of adultery. When viewed in terms of the definition of adultery in Qanun No. 14 of 2003 on Khalwat (Mesum), Enakmen Jenayah Syari'ah Selangor Number 9 of 1995 and Kanun Jenayah Syari'ah Brunei Darussalam 2013, both are not contrary to the provisions of jinayah fiqh. All three have similarities in determining the elements of a criminal act of adultery, namely the element without a legal marriage bond is one of the elements that determine an act of adultery, because if the relationship is based on a legal marriage then automatically the conditions in a marriage have been fulfilled and the relationship is a permissible act